Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Albafurans D−N, 2-phenylbenzofuran derivatives with anti-inflammatory activity from Morus alba - Jun-Sheng Zhang; Lin-Lin Tian; Quan-Hao Wei; Meng-Jie He; Hua Zhang (Phytochemistry, 2026)

Co-degradation detoxification of dichloromethane and n-hexane in a microbial electrolytic cell: metagenomic insights into degradation pathways and functional genes - Meng Wu; Hongfeng Lu; Wenjun Lin; Jun Hu; Zhiliang Yu; Jianming Yu (Journal of Environmental Chemical Engineering, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Cometabolic defluorination of two poly-fluoroalkyl substances by a new Sphingopyxis isolate - Zhaozhao Gao; Xingjia Xiang; Meng Yan; Yongqi Liu; Yucheng Wu; Xin Song; Xiangui Lin; Frank E. Löffler; Jun Zeng (Water Research, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

A DESN-based federated learning framework for NIR spectral analysis of organic carbon in farmland soils - Huazhou Chen; Jun Xie; Bin Lin; Lili Xu; Fangxiu Meng; Guoqiang Tang (Computers and Electronics in Agriculture, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Interfacial electronic coupling phase transition engineering of cobalt-based heterostructures for promoting high-efficiency electromagnetic absorption response - Jun Zhou; Xiaohang Ma; Lin Wang; Ying Meng; Shibin Lu; Zhenfa Zi; Wei Jiang (Chemical Engineering Journal, 2025)

3-hydroxykynurenine increase in kynurenine pathway driven bisphenol F induced anxiety- and depression-like behaviors - Yuxin Lin; Luyao Wang; Sining Meng; Jianjia Liu; Xinyu Li; Wenjuan Wang; Miaoyang Hu; Xi Wang; Weixia Duan; Shangcheng Xu; Jun Wang; Rong Gao (Science of The Total Environment, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Direct and indirect effects of spring phenology on forest transpiration - Lvlv Wang; Dunxian She; Yuting Yang; Lin Meng; Jun Xia (Agricultural and Forest Meteorology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Differential effects of biochar and straw incorporation on soil organic carbon: A case study on paddy cultivation in Northeast China - Hechong Yuan; Yaman Wu; Yuanyuan Sun; Juying Liu; Li Lin; Fan Xia; Xu Su; Qiang Sun; Jun Meng (Journal of Environmental Management, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Atmospheric CO2 and CH4 observations in Hangzhou before, during, and after the 2023 Asian Games: Insights from vehicle-carried and fixed stations - Tianhao Wang; Jiansen Wang; Ning Hu; Ruonan Li; Meng Shan; Qun Lin; Longlong Chen; Jun Wang; Yuxin Jiang; Zhonghao Yang; Wei Xiao (Atmospheric Pollution Research, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Exposure to polyethylene terephthalate micro(nano)plastics exacerbates inflammation and fibrosis after myocardial infarction by reprogramming the gut and lung microbiota and metabolome - Xin Gu; Zhixuan Zhang; Lin Zhao; Lijie Lu; Xin Lu; Yafei Li; Tianya Gu; Xin Huang; Guangyi Huang; Yan Liang; Haoyu Meng; Baihong Li; et al. (Journal of Hazardous Materials, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Improving thermal comfort and cognitive ability of manual workers by cooling garment of different temperatures based on EEG analysis - Haiying Wang; Renjie Yan; Huxiang Lin; Junli Sun; Hang Meng; Rongfu Hou; Yongwang Hao; Songtao Hu; Jun Zhang (Energy and Buildings, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Dissolved organic carbon can alter coastal sediment phosphorus dynamic: Effects of different carbon forms and concentrations - Shuo-Nan Ma; Xu-Meng Dong; Ji-Lin Xu; Chun-Pu Zhao; Miao Liu; Hai-Jun Wang; Erik Jeppesen (Chemosphere, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Enhancing agricultural productivity with biochar: Evaluating feedstock and quality standards - Guiying Lin; Yiying Wang; Xiaodong Wu; Jun Meng; Yong Sik Ok; Chi-Hwa Wang (Bioresource Technology Reports, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Deciphering the inhibitory mechanisms of didecyldimethylammonium chloride on microalgal removal of fluoxetine: Insights from the alterations in cell surface properties and the physio-biochemical and molecular toxicity - Zhengxin Xie; Lin Pan; Meng Nie; Guiyuan Cai; Hebin Liang; Jun Tang; Xiaoli Zhao (Science of The Total Environment, 2025)

A comprehensive evaluation of lightning location accuracy using a weighted gridding method - Lin Song; Qingda Li; Jun Yang; Qilin Zhang; Jie Li; Shudong Wang; Yuqing Zhong; Zhiren Zhou; Meng Zheng (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Trimetallic-doped carbon nitride achieves chondroitin sulfate degradation via a free radical degradation strategy - Xiao-jun Lin; Meng-ting Chang; Min Cao; Muhammad Sohail; Meng Qiao; Xing Zhang (Carbohydrate Polymers, 2024)

Textural properties prediction of KOH-activated carbon prepared from coal based on pyrolysis kinetics - Kai Wang; Guoxin Lin; Jun Meng; Jiangmin Guo; Bo Tan; Shaojun Liu; Qingyang Lin; Xuecheng Wu; Xiang Gao (Waste Disposal & Sustainable Energy, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Pseudoalteromonas flavipulchra as a dual-functional probiotic for aquaculture: enhancing microalgae growth and antagonizing Vibrio pathogens - Min-nan Wu; Yi-jun Xu; Meng-meng Shao; Zi-yue Wang; Jia-yi Cao; Ji-lin Xu (Frontiers in Marine Science, 2024)
Vibrio disease is a prevalent bacterial infection in aquaculture, and using bacteria with antagonistic properties against Vibrio species as probiotics has emerged as a promising method for disease prevention. Additionally, low biomass productivity of microalgae feed remains a significant bottleneck in bivalve aquaculture. Therefore, it is essential to screen for bacteria that both enhance microalgae growth and inhibit Vibrio pathogens. In this study, seven bacterial strains capable of promoting microalgae growth were screened for their ability to inhibit three Vibrio pathogens, i.e., Vibrio vulnificus, Vibrio parahaemolyticus and Vibrio cholerae , and thus serve as a dual-functional probiotic for aquaculture. The antagonistic mechanism of these bacteria was further investigated by analyzing the inhibitory effects of their extracellular products (ECP) on Vibrio species. Results indicated that Pseudoalteromonas flavipulchra exhibited antagonistic effects against all three Vibrio species tested. The ECP of P. flavipulchra displayed stable antibacterial activity, though this ability was lost after the ECP was treated with heat, alkali, or proteinase K. The proteinaceous fraction isolated from the ECP by precipitation with 90% saturated ammonium sulfate demonstrated concentration-dependent antibacterial activity. These findings suggest that P. flavipulchra could serve as a promising dual-functional probiotic for aquaculture, warranting further research to optimize its application in this field.

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Evaluating soil freezing characteristic curve models for predicting unfrozen water content in freezing soils - Fanshuo Meng; Qian Chen; Jun Du; Yumo Wu; Zhikun Lin; Jiaqi Tian; Chong Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Uncertainty of canopy interception modeling in high-altitude Picea crassifolia forests of Semi-arid regions - Junjun Yang; Zhibin He; Pengfei Lin; Jun Du; Dong Shi; Meng Bai (Agricultural and Forest Meteorology, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Enhancing extracellular monascus pigment production in submerged fermentation with engineered microbial consortia - Song Zhang; Meng Shu; Zihan Gong; Xinyi Liu; Chenyu Zhang; Ying Liang; Qinlu Lin; Bo Zhou; Ting Guo; Jun Liu (Food Microbiology, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Mechanical behavior and performance evolution of railway ballast track under dynamic stabiliser based on the hybrid MBD-DEM simulation - Jun Fang; Chunfa Zhao; Changsheng Cai; Chunjun Chen; Can Shi; Meng Lin (Transportation Geotechnics, 2024)

Boosted outputs and robustness of polymeric tribovoltaic nanogenerator through secondary doping - Jia Meng; Chuntao Lan; Chongxiang Pan; Jun Yang; Xiong Pu; Zhong Lin Wang (Chemical Engineering Journal, 2024)

Positive effects of biochar application and Rhizophagus irregularis inoculation on mycorrhizal colonization, rice seedlings and phosphorus cycling in paddy soils - Yixuan CHEN; Zhonghua WEN; Jun MENG; Zunqi LIU; Jialong WEI; Xiyu LIU; Ziyi GE; Wanning DAI; Li LIN; Wenfu CHEN (Pedosphere, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

A mechanism-guided machine learning method for mapping gapless land surface temperature - Jun Ma; Huanfeng Shen; Menghui Jiang; Liupeng Lin; Chunlei Meng; Chao Zeng; Huifang Li; Penghai Wu (Remote Sensing of Environment, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Deciphering the effects of crop rotation on tobacco bacterial wilt through general and specific disease suppression - Hai-kun Ma; Zhi-jiang Wang; Meng-jiao Li; Qing-lin Rao; Jun Cai; Xiao-fei Gu (European Journal of Plant Pathology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

A mild and efficient sonothermal tumor therapy enhanced by sonodynamic effect with biodegradable red phosphorus nanoparticles - Zhizi Ma; Meng Yuan; Ziyong Cheng; Zhuang Yang; Ling Yang; Bin Liu; Yulong Bian; Abdulaziz A. Al Kheraif; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2024)

Eminent destruction of organics and pathogens concomitant with power generation in a visible light-responsive photocatalytic fuel cell with NiFe2O4/ZnO pine tree-like photoanode and CuO/Cu2O nanorod cathode - Sze-Mun Lam; Jin-Chung Sin; Meng Wei Warren Tong; Honghu Zeng; Haixaing Li; Liangliang Huang; Hua Lin; Jun-Wei Lim (Chemosphere, 2023)

Effects of soil amendments on Cd and As mobility in the soil-rice system and their distribution in the grain - Xiao Tan; Yinjie Zhang; Meng Ren; Hantong Qie; Meng Liu; Jun Cui; Dongpo Liu; Chunlei Jiao; Aijun Lin (Science of The Total Environment, 2023)

Cover Crops Control Weed and Improve Soil Qualities in Citrus Orchard - Hang Li; Xun Wang; Yuan Li; Yuhui Hou; Ziming Zhao; Lin Meng; Ji Liu; Jun Wang; Bo Xiong; Zhihui Wang (Journal of Soil Science and Plant Nutrition, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Behavior of 3D-printed HPC plates with FRP grid reinforcement under bending - Jun-Jie Zeng; Pei-Lin Li; Zi-Tong Yan; Jie-Kai Zhou; Wai-Meng Quach; Yan Zhuge (Engineering Structures, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Scour effects on the vertical dynamic response of single piles in transversely isotropic soils - Chun Lin Liu; Zhi Yong Ai; Meng Xiong Tang; He Song Hu; Lu Jun Wang (Ocean Engineering, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Linking peptide-oriented surface imprinting magnetic nanoparticle with carbon nanotube-based fluorescence signal output device for ultrasensitive detection of glycoprotein - Shi-Song Yu; Yu-Jun Shi; Di Wang; Ti-Ti Qiang; Ya-Qi Zhao; Xin-Yu Wang; Jia-Meng Zhao; Lin-Yi Dong; Ya-Jie Huang; Xian-Hua Wang (Analytica Chimica Acta, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Arsenic removal and stabilization behavior of schwertmannite@BC (Sch@BC) in contaminated dual media (water/soil): Via sulfate exchange and chemical complexation - Xiao Tan; Jiahao Liu; Meng Liu; Yinjie Zhang; Qi Liu; Guilan Duan; Jun Cui; Aijun Lin (Environmental Pollution, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Rational design of Multi-model ROS regulation Nano-platform for enhanced Mild-temperature photothermal therapy - Wenying Zhang; Meifang Wang; Bin Liu; Meng Yuan; Zhuang Yang; Jia Tan; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Gold − Titanium dioxide heterojunction for enhanced sonodynamic mediated biofilm eradication and peri-implant infection treatment - Fang Li; Qiyuan Pan; Yun Ling; Jingying Guo; Yaru Huo; Chao Xu; Manwen Xiong; Meng Yuan; Ziyong Cheng; Min Liu; Jun Lin (Chemical Engineering Journal, 2023)

The formation of discharge standards of pollutants for municipal wastewater treatment plants needs adapt to local conditions in China - Yinjie Zhang; Jun Cui; Congbin Xu; Jingjing Yang; Meng Liu; Meng Ren; Xiao Tan; Aijun Lin; Wenjie Yang (Environmental Science and Pollution Research, 2023)

Revegetation affects the response of land surface phenology to climate in Loess Plateau, China - Lvlv Wang; Dunxian She; Jun Xia; Lin Meng; Lingcheng Li (Science of The Total Environment, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Modified biochar/humic substance/fertiliser compound soil conditioner for highly efficient improvement of soil fertility and heavy metals remediation in acidic soils - Meng Liu; Xiao Tan; Mingxia Zheng; Dayang Yu; Aijun Lin; Jiaoxian Liu; Chunyan Wang; Zhiyun Gao; Jun Cui (Journal of Environmental Management, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

High-efficiency control of pesticide and heavy metal combined pollution in paddy soil using biochar/g-C3N4 photoresponsive soil remediation agent - Hantong Qie; Meng Ren; Chang You; Xuedan Cui; Xiao Tan; Yuting Ning; Meng Liu; Daibing Hou; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Cross-generation trophic ecology of Dosidicus gigas in the eastern-central Pacific Ocean revealed from isotopic signatures in eye lenses - Guan Yu Hu; Zi Xin Wang; Bi Lin Liu; Meng Yao Huan; Xin Jun Chen (Fisheries Science, 2022)

Effects of Microplastics on Microbial Community in Zhanjiang Mangrove Sediments - Meng-Meng Chen; Fang-Hong Nie; Aftab Qamar; Di-hua Zhu; Yao Hu; Min Zhang; Qing-Lang Song; Hong-Ying Lin; Zhi-Bao Chen; Su-Qing Liu; Jin-Jun Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Pilot study on the treatment of low carbon and nitrogen ratio municipal sewage by A1/O2/A3/A4/O5 sludge-membrane coupling process with multi-point inflow - De-Wei Zhang; Jun-Tian Zheng; Jun Zheng; Meng-Ke Zhao; Meng-Lin Wang; Shi-Hua Zhang (Environmental Science and Pollution Research, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Long-term influence of maize stover and its derived biochar on soil structure and organo-mineral complexes in Northeast China - Qiang Sun; Jun Meng; Binoy Sarkar; Yu Lan; Li Lin; Haifeng Li; Xu Yang; Tiexin Yang; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Rock mass permeability classification schemes to facilitate groundwater availability assessment in mountainous areas: a case study in Jhuoshuei river basin of Taiwan - Shih-Meng Hsu; Jun-Pu Hsu; Chien-Chung Ke; Yen-Tsu Lin; Chi-Chao Huang (Geosciences Journal, 2020)

Responses of soil moisture to regional climate change over the Three Rivers Source Region on the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Zhaoguo Li; Yaqiong Lyv; Huajin Lei; Lin Zhao; Shengnan Zhao; Jun Ge; Hui Jing (International Journal of Climatology, 2020)
In this study, soil moisture data from two reanalysis datasets (ERA‐Interim, ERA5), a satellite soil moisture product from the European Space Agency (ESA) and three assimilation datasets from the Global Land Data Assimilation System (GLDAS), that is, GLADS‐NOAH025, GLADS‐NOAH10, and GLDAS‐CLM were compared with the observed soil moisture data in Maqu and Maduo stations over the Three Rivers Source Region (TRSR) on the Tibetan Plateau in China. Comparative statistical parameters between the soil moisture observations and the products, including the root mean square error, correlation coefficient ( R ), and standard deviation ratio were calculated to evaluate the products in different seasons. It was found that most products overestimated the soil moisture values, among which GLADS‐NOAH025 had relatively good consistency with the observations in the surface soil layer (0–10 cm), whereas GLDAS‐CLM agreed well with the observations in the 10–40 cm layer. Both ERA5 and ERA‐interim soil moisture overestimated soil moisture at all levels. The responses of soil moisture to regional climate change over the TRSR were also investigated by using the GLDAS‐NOAH025 soil moisture product, the ESA soil moisture product, and the observations during the nonfreezing period. The results show that the trends of soil moisture are consistent with the precipitation changes in the main central part of the TRSR. A significant positive correlation was found between soil moisture and precipitation in most regions of the TRSR, which indicates that soil moisture increases with the increase of precipitation, except in the northwest TRSR, where the variation of soil moisture was possibly influenced by both the precipitation changes and the increase of evapotranspiration.

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Phylogenetic analysis of upland cotton MATE gene family reveals a conserved subfamily involved in transport of proanthocyanidins - Lei Xu; Zhi-Lin Shen; Wen Chen; Guo-Yang Si; Yan Meng; Ning Guo; Xu Sun; Yong-Ping Cai; Yi Lin; Jun-Shan Gao (Molecular Biology Reports, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Gene locations may contribute to predicting gene regulatory relationships - Jun Meng; Wen-yuan Xu; Xiao Chen; Tao Lin; Xiao-yu Deng (Journal of Zhejiang University-SCIENCE B, 2018)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Characterization, sources and ecological risk assessment of polycyclic aromatic hydrocarbons in surface sediments from the mangroves of China - Dao-lai Zhang; Na Liu; Ping Yin; Zhi-gang Zhu; Jing-fang Lu; Xue-hui Lin; Xue-jun Jiang; Xian-wei Meng (Wetlands Ecology and Management, 2017)

Copy Number Variations in Tilapia Genomes - Bi Jun Li; Hong Lian Li; Zining Meng; Yong Zhang; Haoran Lin; Gen Hua Yue; Jun Hong Xia (Marine Biotechnology, 2017)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation - Quan-jun Zhang; Shu-tian Tao; Meng Li; Xiao-xiao Qi; Jun Wu; Hao Yin; Jia-lin Deng; Shao-ling Zhang (Tree Genetics & Genomes, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Within-litter variation in birth weight: impact of nutritional status in the sow - Tao-lin Yuan; Yu-hua Zhu; Meng Shi; Tian-tian Li; Na Li; Guo-yao Wu; Fuller W. Bazer; Jian-jun Zang; Feng-lai Wang; Jun-jun Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Sensitivity analysis of the hydrological response of the Gaping River basin to radar-raingauge quantitative precipitation estimates - Tsung-yi Pan; Meng-ying Li; Yong-jun Lin; Tsang-jung Chang; Jihn-sung Lai; Yih-chi Tan (Hydrological Sciences Journal, 2014)

Fractured-bedrock aquifer studies based on a descriptive statistics of well-logging data: A case study from the Dajia River basin, Taiwan - Po-Yi Chou; Shih-Meng Hsu; Po-Jui Chen; Jung-Jun Lin; Hung-Chieh Lo (Acta Geophysica, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Nitric oxide acts as a signal molecule in microwave pretreatment induced cadmium tolerance in wheat seedlings - Zong-Bo Qiu; Jun-Li Guo; Man-Man Zhang; Meng-Yun Lei; Zhen-Lin Li (Acta Physiologiae Plantarum, 2013)

A new triterpenoid saponin from Gynostemma pentaphyllum - Lin Shi; Xian-Jun Meng; Jia-Qing Cao; Yu-Qing Zhao (Natural Product Research, 2012)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Expression analysis of shikonin-biosynthetic genes in response to M9 medium and light in Lithospermum erythrorhizon cell cultures - Wen-Ju Zhang; Jing Su; Meng-Yue Tan; Gen-Lin Liu; Yan-Jun Pang; Heng-Guan Shen; Jin-Liang Qi; Yonghua Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Streptomyces nanningensis sp. nov. a novel Streptomycete from forest soil - Yi Jiang; Wen-Jun Li; Ping Xu; Ming-Gang Li; Meng-Liang Wen; Guan-Hua Du; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Streptomyces roseoalbus sp. nov., an actinomycete isolated from soil in Yunnan, China - Li-Hua Xu; Yi Jiang; Wen-Jun Li; Meng-Lang Wen; Ming-Gang Li; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)